2009
DOI: 10.1352/2009.114.100-109
|View full text |Cite
|
Sign up to set email alerts
|

T Lymphocyte Maturation Is Impaired in Healthy Young Individuals Carrying Trisomy 21 (Down Syndrome)

Abstract: Cytokine production, immune activation, T lymphocytes maturation, and serum IL-7 concentration were examined in 24 youngsters with Down syndrome and no acquired diseases (healthy Down syndrome [12 prepubertal, 13 pubertal]) and 42 age- and gender-matched controls (20 prepubertal, 22 pubertal). Results showed that a complex immune and impairment is present in healthy individuals with Down syndrome in whom interferon gamma, interleukin (IL) IL-10 production, as well as serum IL-7 concentrations and activation ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Alteration in the immune system, such as functional and morphological thymus abnormalities (Bloemers et al, 2011;Karl et al, 2012), lymphocytopenia, and alteration in differentiation, maturation, and activation of the T lymphocyte (Guazzarotti et al, 2009;Lorenzo et al, 2013) is frequently observed in DS individuals (Kusters et al, 2009). It can be responsible for increased incidence of infections, mainly in the respiratory tract (Bloemers et al, 2010;Broers et al, 2012), and occurrence of autoimmune disease in DS (Gillespie et al, 2006;Pellegrini et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Alteration in the immune system, such as functional and morphological thymus abnormalities (Bloemers et al, 2011;Karl et al, 2012), lymphocytopenia, and alteration in differentiation, maturation, and activation of the T lymphocyte (Guazzarotti et al, 2009;Lorenzo et al, 2013) is frequently observed in DS individuals (Kusters et al, 2009). It can be responsible for increased incidence of infections, mainly in the respiratory tract (Bloemers et al, 2010;Broers et al, 2012), and occurrence of autoimmune disease in DS (Gillespie et al, 2006;Pellegrini et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The cytokines belong to a diversified group of protein, which participated in various biological processes, including the mediation of the inflammatory response (Zhang and An, 2007). Changes in the concentration of proinflammatory and anti-inflammatory cytokines in DS individuals demonstrate its association with the syndrome pathogenesis (Tsilingaridis et al, 2003;Guazzarotti et al, 2009;Cetiner et al, 2010;Broers et al, 2012Broers et al, , 2014. The study of Cetiner et al (2010) observed that the IL6 serum levels were lower in DS children compared with individuals without the syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunological investigation of a small number of DS patients with tuberculosis (TB) has shown no consistent defect [7]. The immune cellular status in children with DS is similar to that of the normal population as far as white blood cell, lymphocyte, CD4(+), CD8(+), natural killer and immunoglobulins are concerned [8], and maturation of T lymphocytes may be impaired in healthy young individuals with DS [9]. Although common, illness in people with intellectual disabilities may be under diagnosed and poorly managed [10].…”
Section: Introductionmentioning
confidence: 99%